Experimental investigation of the thermal performance of heat pipe assisted phase change material for battery thermal management system. (August 2018) - Huang, Qiqiu; Li, Xinxi; Zhang, Guoqing; Zhang, Jiangyun; He, Fengqi; Li, Yang
Graphical abstract: The Figure displayed the schematic illustrations of designed battery module and sub-modules. Towards to PCM/HP-Air cooling system, the air passes through the capillary tube to increase the heat dissipation of the phase-change material. For PCM/HP-Liquid cooling system, the working medium was ethyl alcohol, the evaporation section of the plate heat pipe was contacted with the PCM, and the condensation section was exposed to the air. When the PCM transported the heat generated from the battery to plate heat pipe, the internal medium would generate the phase transformation heat from the evaporation section to condensation section, the liquid in the heat pipe flows repeatedly as this working principle. Highlights: A serials PCM based thermal management systems were investigated by experiments. PCM with large heat storage capacity can balance the temperature of battery module. Heat pipe with high heat conductivity assisted PCM can keep battery working normally. Heat pipe assisted PCM coupled with liquid cooling system was an efficient BTMS. Abstract: In this study, a serials phase change materials (PCM) based battery thermal management systems for cylindrical lithium battery module were designed, which were pure PCM, heat pipe coupled with air assisted PCM (PCM/HP-Air), heat pipe coupled with liquid assisted PCM (PCM/HP-Liquid), respectively. The PCM with large heat storage capacity and heat pipe coupled with liquid cooling exhibit excellent thermal performance for battery module, which is an effective and reliable method with relative longer working time and appropriate temperature. The results by experiments at different discharge rates indicated that heat pipe played an important role in transporting the heat promptly and balancing the temperature uniformly for PCM based battery module. What's more, the heat pipe coupled with liquid cooling presented a remarkable controlling temperature capacity, the highest temperature could be maintained at 50 °C during 3 C discharge rate. Meanwhile, a lower temperature difference of the PCM/HP-Liquid than the other two modules was obtained by nearly 3 °C, which displayed a prominent balancing temperature effectiveness. It could be concluded that the above results can provide perspectives in designing and optimizing battery thermal management system.